Existence of Th22 in children and evaluation of IL-22 + CD4 + T, Th17, and other T cell effector subsets from healthy children compared to adults. (December 2016) - Shen, Erxia; Wang, Mengjie; Xie, Hairui; Zou, Ruqiong; Lin, Qiwen; lai, Lili; Li, Fujun; Liang, Zhimei; Xu, Yanran; Zhou, Maohua
Abstract Background Children are prone to get infections, especially in the respiratory system and the gut mainly because their immune system is immature. T cells significantly contribute to the prevention of infections, and different helper T cell (Th) subsets play different anti-pathogen roles. Interleukin (IL)-22 producing by T-helper 22 cells (Th22) play an important role in host defense against Gram-negative bacterial organisms in gut and lung. T-helper 17 cells (Th17) protect against extracelluar bacteria and fungi especially at the epithelial surface. However, there is no report comparing IL-22 producing T cells and Th17 cells in healthy young children to adults. Methods Flow cytometry (FCM) was used to observe whether Th22 subset existed in the peripheral blood of healthy young children. Meanwhile, we determined the frequencies of Th subsets including Th17, Th1 and Th2, cytotoxic T (Tc)1 subset, CD4+ and CD8+ memory T cells in the peripheral blood of both young children and adults. Results In the present study, we demonstrated that Th22 subset existed in peripheral blood of children, with IL-22 mainly secreted by CD4 + CD45RO+ memory T cells. Moreover, we observed that IL-22 + CD4 + T cells and Th subsets including Th17, Th1, and Th2 frequencies of young children (1–6 years old) were significantly lower than adults. While the Th1 frequency from Group A (1–3 years old) was markedly lower than that from Group B (4–6 years old). No significant differences of Th17 or IL-22 + CD4 + T cells frequencies were observed between these two groups. In addition, Tc1 subset frequencies were also remarkably lower in young children than in adults. Furthermore, lower frequencies of CD45RO+ memory CD4+ and CD8+ T cells in young children than in adults, and significant correlation between CD45RO+ memory CD4 + T cells and IL-22 + CD4 + T cells, Th1, Th17 were observed. Conclusions Th22 subset exists in the peripheral blood of young children. Compared with adults, there are lower frequencies of IL-22 + CD4 + T cells, as well as Th1, Th17, Th2 and Tc1 subsets in the peripheral blood of young children.